Oral Reading Fluency (ORF) Method to Improve Arabic Reading Comprehension - Mauludiyah, Lailatul (IAIN Salatiga, 2020)
The purpose of this study was to describe the use of the Oral Reading Fluency (ORF) method and to show the effectiveness of its use in Arabic reading at Muhamamdiyah University Malang. The method used in this research was descriptive quantitative with the Arabic education department students as the objects. The instruments used for the data collection were questionnaire and observation sheet, while the data analysis used the percentage of student responses. This research was conducted on four meetings. Each meeting had different text with a range of 125 - 140 words and a different final evaluation. This method implements a bear-back manner of reading quickly and at a specified time. The results of this study indicated that the ORF method is very helpful for students to be able to read Arabic texts fluently and accurately. It is proven that 50% of students give positive response to the application of this method. This method can also help improve the ability to understand the contents of Arabic text which has been one of the problems in learning Arabic language skills. It was proven that at the end of the meeting 85% of students completed the material with perfect scores.